Study abroad programs provide opportunities for students to develop their academic abilities, language skills, and cross-cultural competence. In the context of Arabic language learning, international experience enables authentic language use alongside the process of cultural adaptation. However, such experiences are still rarely examined in depth from both academic and cultural perspectives. Therefore, this study aims to explore the international experiences of students in the ITHLA Abroad Batch - Najih Hariadi (Al-Jawhar : Journal of Arabic Language, 2026)
Study abroad programs provide opportunities for students to develop their academic abilities, language skills, and cross-cultural competence. In the context of Arabic language learning, international experience enables authentic language use alongside the process of cultural adaptation. However, such experiences are still rarely examined in depth from both academic and cultural perspectives. Therefore, this study aims to explore the international experiences of students in the ITHLA Abroad Batch 7 program from both academic and cultural perspectives. This study uses a qualitative approach with a descriptive method. The research subjects are students participating in the ITHLA Abroad program, with data collection techniques through interviews, observations, and documentation. Data analysis is carried out using the Miles and Huberman interactive model, which includes data reduction, data presentation, and conclusion drawing. The results of the study show that from an academic perspective, there is a shift in learning Arabic from being theoretical to more practical and contextual through direct interaction with native speakers, thereby improving students' communicative abilities and self-confidence. From a cultural perspective, students undergo a process of adapting to cultural differences that initially causes difficulties but can gradually be overcome through social interactions in the new environment. This study also found that academic and cultural experiences are integrated in supporting language learning success and the development of students' global competence. Thus, the ITHLA Abroad program becomes an experience-based learning tool that is effective in holistically developing linguistic and intercultural competence.